First light - Stead, Rebecca (Wendy Lamb Books : Random House/Yearling, 2007)
When twelve-year-old Peter and his family arrive in Greenland for his father's research, he stumbles upon a secret his mother has been hiding from him all his life, and begins an adventure he never imagines possible.